2015
DOI: 10.52964/amja.0529
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Outpatient Management of patients with low risk febrile neutropaenia

Abstract: Patients with febrile neutropenia are a heterogeneous group with only a minority developing significant medical complications. Scoring systems, such as the Multinational Association for Supportive Care in Cancer (MASCC) score, have been developed and validated to identify low risk patients. Caring for patients with low risk febrile neutropenia in an ambulatory setting is proven to be safe and effective. Benefits include admission avoidance, cost savings and reduced risk of nosocomial infections, as well as imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…4,7 This can then be used to identify those patients who are potentially suitable for early-supported discharge and management in an ambulatory setting. 10,11 The re-admission rate in our study was 10% and none of the patients required escalation to critical care. This is in line with published literature, which shows a re-admission rate of 5-20%.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…4,7 This can then be used to identify those patients who are potentially suitable for early-supported discharge and management in an ambulatory setting. 10,11 The re-admission rate in our study was 10% and none of the patients required escalation to critical care. This is in line with published literature, which shows a re-admission rate of 5-20%.…”
Section: Discussionmentioning
confidence: 50%
“…9 A number of studies have investigated using the MASCC score to identify patients who are at low risk, by having a MASCC score ≥21, and therefore could be considered for management in an ambulatory setting. 10,11 This has been shown to be a safe and cost effective way to manage these patients. 12,13 In the Oncology community this scoring system has been in place for many years but is still in its infancy amongst non-specialist hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Outpatient ambulatory care for emergency patients with a low-risk febrile neutropenia has already been proven as safe and effective [27]. However, there are challenges regarding the delivery of outpatient care that can mean it is not feasible for all patients, with transport issues being a key constraint [15].…”
Section: Discussionmentioning
confidence: 99%
“…Neutropenia is a common side effect of conventional cytotoxic chemotherapy, with standard-dose regimens typically causing a nadir around 7-10 days, which can incur around 7 days of neutropenia [14]. There are thought to be around 8 cases per 1000 patients who are receiving chemotherapy who develop neutropenic sepsis [15]. Improved management of neutropenic sepsis has been shown to improve morbidity and mortality rates [16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This has included management of low-risk NS although it has only been implemented by a limited number of UK cancer centres. 40,41 Some have reported results from longitudinal patient series. Marshall et al 42 reported a series of 100 patients from a large UK tertiary cancer centre over a 2-year period with NS who were assessed and given a first dose of i.v.…”
Section: Acute Oncology Service Developmentmentioning
confidence: 99%